Effects of N-Acetylcysteine on Meteorin-like Protein and Asprosin in an Experimental Lower Extremity lschemia-Reperfusion Injury Model - Ozguler, Ibrahim Murat; Ustunel, Latif (Sci Printers & Publ Inc, 2021)
OBJECTIVE: To investigate the effects of N-acetylcysteine (NAC) on meteorin-like protein (METRNL) and asprosin in an experimental lower extremity ischemiareperfusion injury model. STUDY DESIGN: Male rats (n=30) were divided into 5 groups. No intervention was applied to the control group. The surgical procedure applied to the sham group was the same as the other groups. A single dose of 150 mg/kg NAC was administered to the rats in the NAC group 120 minutes before the end of the experiment. In the ischemia-reperfusion (I/R) group the infrarenal abdominal aorta was exposed by immobilizing the rats in the supine position and performing laparotomy in the midline of the abdomen. The aorta was later clipped using a nontraumatic microvascular clamp for 120 minutes, followed by opening the clips and terminating the experiment after 120 minutes of reperfusion. The I/R + NAC group underwent the surgical procedure and then was administered a single dose of 150 mg/ kg NAC, and the experiment was terminated after 120 minutes of reperfusion. At the end of the experiment, following intracardiac blood collection under anesthesia from the rats of all groups, muscle tissues of the lower extremity were removed rapidly. Serum levels of total oxidant status, asprosin, and METRNL were measured with ELISA. Immunohistochemical staining was performed for asprosin and METRNL. RESULTS: Serum and tissue METRNL and asprosin levels in the I/R group were lower as compared with the control group. These values were higher in the I/R+ NAC group as compared with the I/R group. CONCLUSION: Asprosin and METRNL can be useful in the diagnosis or treatment of ischemic lower extremity injuries.
Keywords: adipokines; asprosin; biomarkers; immunohistochemistry; ischemia; N-acetylcysteine; mesothelioma; meteorin-like; meteorin; reperfusion